Biology-specific vocabulary: students' understanding and lecturers' expectations of student understanding. Issue 4 (8th August 2019) - Jones, Harriet L; Green, Jon R; Prendergast, John; Scott, Jon
Abstract: The current A-level biology curriculum includes a broad coverage of all the biosciences which demands knowledge of a wide range of biological vocabulary. Students ( n  = 184) from two UK universities were presented with a list of vocabulary, associated with a 'Revise Biology' text which highlighted key terms that students should know. Lecturers ( n  = 26) were asked which of these terms they expected students to know, or be aware of. Findings revealed that students' claimed knowledge of vocabulary exceeded lecturer expectations. In addition, there were a number of terms which students did not understand and lecturers did not expect them to know, which could be removed from A-level biology courses. This is discussed in relation to whether A-level curricula need to be so content heavy and whether lecturers would benefit from knowing more about their students' knowledge of discipline-specific terms.